IMPLEMENTATION OF THE VALUES OF RELIGIOUS MODERATION IN PAI LEARNING AT MADRASAH AND ISLAMIC RELIGIOUS COLLEGE - Huda, Miftahul; Kurnia, Asep; Arifin, Bambang Samsul; Ruswandi, Uus (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
This research tries to examine the implementation of religious moderation values in PAI learning at Madrasahs and Islamic Religious Colleges (PTKI) as an answer to problems related to the many statements that our educational institutions are currently exposed to radicalism and intolerance. By using qualitative methods and library research techniques this study concludes that the implementation of religious moderation values in PAI learning in Madrasahs and Islamic Religious Colleges (PTKI) can be pursued in 3 (three) strategies as follows: 1) inserting (insert) moderation content in each relevant material, 2) optimizing learning approaches, and 3) organizing certain programs, education, training and debriefing with a special theme on religious moderation.